Certain aspects of the use of the escrow agreement in the implementation of the squeeze-out procedure - Zozuliak , Olha; Hlavach , Iryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The scientific article examines the legislative consolidation of the mechanism for using the conditional storage account agreement (escrow) in the implementation of the squiz-out procedure. This is necessary to ensure the fulfillment of the dominant shareholder’s right to repurchase shares while not restricting the rights of minority shareholders to receive payments for their shares. The critical aspects of implementing this contractual structure are considered, in particular, the legal nature of escrow, its role in ensuring security and trust in implementing the squiz-out procedure, and the advantages and risks associated with its use in such procedures. The positive experience of regulating this institute in the legislation of European countries and ways of its implementation in the current legislation of Ukraine are analyzed. This indicates the mixed legal nature of the escrow agreement. It is noted that the provisions of the current civil legislation need to be improved in terms of regulating the beneficiary’s participation as a party to the escrow agreement and improving the regulation of the terms for depositing and crediting funds to the account. The necessity of improving the procedural aspects in implementing bank payments in the studied legal relations is argued, particularly in terms of the legislative expansion of the list of grounds on which funds can be transferred to a person who is not a beneficiary under the escrow agreement. It is indicated that the tendency to detail the clauses of the contract escrow the grounds and forms of responsibility of the parties to the contract for its non-fulfillment or improper execution.